Public sentiment is everything: Host-country public sentiment toward home country and acquisition ownership during institutional transition - Yiu, Daphne W.; Wan, William P.; Chen, Kelly Xing; Tian, Xiaocong (Journal of International Business Studies, 2022)
Under strict scrutiny of public governance primed by international relation tensions, geopolitics, and the rise of social movements and public activism in the globalized economy, public sentiment is exerting increasing pressure on multinational corporations (MNCs). Utilizing the context of inward acquisition, a sensitive cross-border action that often triggers sentiment of host-country nationals, we theorize from the public sentiment perspective and the public thermostat analogy that foreign acquirers will adjust their ownership levels in target firms according to how they perceive to be acceptable and legitimate as expressed by host-country nationals’ public sentiment toward their home country. Using a sample of 410 acquisition deals from 22 foreign countries/economies into China during 2010–2017 and a sentiment analysis of 100,902 blog posts, we find that a host country’s public sentiment toward the acquiring firm’s home country is positively related to acquisition ownership levels, and has a mutualistic symbiotic interaction with the host region’s marketization level. Our study contributes to the study of informal institutions by proposing public sentiment as a new form of informal institution that is normative-cognitive whilst affective, and can be mobilized and communicated broadly and timely via a public sphere to confer social, political, and cognitive legitimacy to MNCs.